Analisis Identivikasi Tingkat Pemahaman Siswa Terhadap Teori dan Praktek Kebugaran Jasmani Siswa Sekolah Menengah Atas - Karsan Suryana; Ega Trisna Rahayu; Siswanto Siswanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
The problem in this study is that the level of understanding of students is not yet known upwards in class XII social studies about physical fitness, while this study aims to find out how high the level of understanding of students in class XII social studies about physical fitness at SMA Negeri 22 Bekasi City. This type of research is quantitative research with a survey method with data collection techniques using tests. This research was carried out with the research subjects of class XII social studies students at SMAN 22 Bekasi City totaling 69 students. The data source was obtained using a questionnaire in the form of test questions totaling 30 valid items with a reliability coefficient of 0.916. The data analysis technique used in this study is a quantitative descriptive statistical analysis technique with percentage calculations. Based on the results of data analysis and discussion, it can be concluded, that the level of understanding of class XII social studies students towards physical fitness at SMA N 22 Bekasi City for the 2022/2023 school year with a sample of 69 students is categorized as follows: very high category with a percentage of 3% as many as 2 students, high category with a percentage of 32% as many as 22 students, medium category with a percentage of 38% as many as 26 students, the low category with a percentage of 23% as many as 16 students and the very low category with a percentage of 4% with 3 students. And there are also results from, 1) Factors for the definition of physical fitness, as many as 12 students (17%) are in the very low category, 0 students (0%) have a low category, 21 students (30%) have a medium category, 0 students (0%) have a high category, while 36 students (52%) have a very high category. 2) Physical fitness component factors as many as 6 students (9%) are in the very low category, 19 students (28%) have a low category, 21 students (30%) have a medium category, 18 students (26%) have a high category, while 5 students (7%) have a very high category. 3) Physical fitness benefit factors as many as 4 students (6%) are in the very low category, 9 students (13%) have a low category, 0 students (0%) have a medium category, 0 students (0%) have a high category, while 56 students (81%) have a very high category. 4) Physical fitness development factors as many as 5 students (7%) are in the very low category, 6 students (9%) have a low category, 24 students (35%) have a medium category, 24 students (35%) have a high category, 10 students (14%) have a very high category. 5) The physical fitness test factor of 3 students (4%) is in the very low category, 23 students (33%) have a low category, 22 students (32%) have a medium category, 0 students (0%) have a high category, while 21 students (30%) have a very high category. From these results, it shows that the level of understanding of class XII social studies students towards physical fitness at SMA N 22 Bekasi City for the 2022/2023 school year is in the medium category with a percentage of 38%. Thus, students still do not fully have a good understanding of Physical Fitness